2021
DOI: 10.15292/acta.hydro.2021.04
|View full text |Cite
|
Sign up to set email alerts
|

After 2000 Stože Landslide: Part II - Development of landslide disaster risk reduction policy in Slovenia

Abstract: More than 20 years after the 2000 Stože Landslide that devastated the village of Log pod Mangartom in NW Slovenia, this paper gives a review of the short-term response to and disaster relief provided for this catastrophic event, and further summarises this event’s effects on Slovenia’s efforts to improve its system of preventing natural disasters caused by various forms of landslides. Recent advances in reducing landslide disasters in Slovenia after 2000 are presented, including hazard and risk maps for landsl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This means that altitude is not a very good predictor of erosivity in the case of Slovenia. The main reason is probably the relatively complex topography and rainfall generation mechanisms that often lead to flash floods or rainfall- induced landslide triggering (Mikoš et al, 2006;Rusjan et al, 2009;Bezak et al, 2015a;Jemec Auflič et al, 2017;Mikoš, 2020bMikoš, , 2020aMikoš, , 2021.…”
Section: Slovenian Stations In the Redes Databasementioning
confidence: 99%
“…This means that altitude is not a very good predictor of erosivity in the case of Slovenia. The main reason is probably the relatively complex topography and rainfall generation mechanisms that often lead to flash floods or rainfall- induced landslide triggering (Mikoš et al, 2006;Rusjan et al, 2009;Bezak et al, 2015a;Jemec Auflič et al, 2017;Mikoš, 2020bMikoš, , 2020aMikoš, , 2021.…”
Section: Slovenian Stations In the Redes Databasementioning
confidence: 99%
“…To improve landslide dynamic models, practices in different parts of the world show that a good understanding of landslide dynamics can be achieved by setting up flexible and reliable monitoring systems [9,[12][13][14][15][16][17]. These systems are used to implement periodic and continuous measurements to monitor changes over time and space.…”
Section: Introductionmentioning
confidence: 99%
“…These events, and the fact that alpine and perialpine regions are highly susceptible to landslides, have revealed that, on the whole, Slovenia needs to pay more attention to landslide prevention measures, to reduce the impact of landslide activity and to protect people and infrastructure (Mikoš, 2021).…”
Section: Introductionmentioning
confidence: 99%